Precise nanoscale fabrication technologies, the “last mile” of medicinal development - Ye Bi; Sensen Xie; Ziwei Li; Shiyan Dong; Lesheng Teng (Acta Pharmaceutica Sinica B)
Nanotechnologies seek to overcome inherent deficiencies of conventional diagnosis and treatment, which attracted sustained attention and a limited number of nanomedicines approved by the FDA. However, the critical gaps in clinical translation remain, and nanomedicines that were initially heralded as magic bullets have yet to reach their realistic potential. The major obstacles of fabrication technologies may be overlooked in the nanoparticles’ journey. Suboptimal manufacturing strategies partly hampered the inefficient transformation. In this review, we discuss the nanoparticle manufacturing strategies of “Top-Down” and “Bottom-Up” on precise nanoscale fabrication, including artificial intelligence introduced to guided nanomedicine fabrication for accelerating the transformation. Re-engineering existing nanomedicine fabrication, individual manufacturing, and modular technology might highlight the dilemmas of nanomedicines to meet their initial expectations.